Theorizing Dependency Relations in Small Media - Semujju, Brian (Communication Theory, 2020)
The paper questions the pervasive western intellectual universalism which disregards Global South imaginations for generalized approaches. Using field data from Uganda about Community Audio Towers (CATs), the western-generated community media theory is interrogated, accentuating its failure to account for the intricate relationship between the individual, society, and small media. To cover the gap, the Small Media System Dependency theory is herein introduced as a geocultural response to lack of theory from the South.
Keywords: Community Audio Towers, Small Media, Small Media System Dependency Theory, Global South, Media System Dependency